“Hear What You Want”: Sonic Politics, Blackness, and Racism-Canceling Headphones - Blue V, Alex (Current Musicology, 2017)
SHOT: A person sits on a couch, book in hand, coffee table at the knees. We have not yet seen their head—the camera has kept their identity con-cealed, showing only the shoulders down. As the camera slowly pans, and the person carefully turns the page in their book, we hear voices being broadcast from a television. The camera switches gaze, turning to show a sports commentator speaking on screen “I think there’s zero threat. My problem is, KG’s a little too ‘over-the-hill’...”